Plasma Levels of Big Endothelin-1 Are Associated with Renal Insufficiency and In-Hospital Mortality of Immune Thrombotic Thrombocytopenic Purpura - Lu, Ruinan; Zheng, X. Long (Thrombosis and Haemostasis, 2021)
Immune thrombotic thrombocytopenic purpura (iTTP) is caused by severe deficiency of plasma ADAMTS13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13) activity. Despite advances in early diagnosis and management, the mortality rate of acute iTTP remains high in a large part of world where access to some of the most novel therapies is limited. To determine the role of plasma big endothelin-1 (bigET-1) or its bioactive product ET-1 as a biomarker and/or a pathogenic factor in acute iTTP, plasma levels of bigET-1 were determined using an immunoassay in patients with iTTP on admission and during remission, as well as in healthy controls; moreover, the biological effect of ET-1 in thrombus formation was determined by a microfluidic assay. We show that plasma levels of bigET-1 were dramatically increased in patients with acute iTTP on admission, which was significantly decreased during clinical response/remission; elevated admission levels of plasma bigET-1 were associated with low estimated glomerular filtration rate, the need for intensive care unit admission or intubation, and in-hospital mortality. Moreover, an addition of a bioactive product ET-1 to cultured endothelial cells in a microfluidic channel significantly accelerated the rate of thrombus formation under arterial flow. Our results demonstrate for the first time a potential role of measuring plasma bigET-1 in patients with acute iTTP in assessing the disease severity and risk of in-hospital mortality, which may help stratify patients for a more aggressive monitoring and therapeutic strategy; also, the bioactive ET-1, derived from bigET-1, may result in acute renal injury in TTP patient, likely through its vasoconstriction and prothrombotic properties.
Keywords: endothelial ET-1; TTP; renal injury; mortality; outcome